2018
DOI: 10.1002/celc.201800565
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Deposition of Enantiopure Hexahelicene Layers

Abstract: Helicenes are polyaromatic compounds with chiral properties useful for many applications in optoelectronics, separation processes, chiral recognition and catalysis. Here we focused on the electrochemistry of carbo[n]helicenes (n=5,6,7). The cyclic voltammograms of racemic mixtures of target compounds in acetonitrile/0.1 M tetrabutylammonium perchlorate at a glassy carbon electrode reveal the diffusion‐controlled reactions in both anodic and cathodic potential regions. Electrochemical behaviors are different fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…There are only two reports on the single molecule conductance properties of uncharged diazahelicenes, where Nheteroatoms served as the anchoring groups. [30,31] In the first work the theoretical description of mechanical tuning of the single molecule conductance was emphasized, whereas in the second one the single molecule conductance of oxa [9]helicene terminated by pyridine units was reported to be 8.8 × 10 À 4 G/G 0 (log(G/G 0 ) = À 3.06), which is in reasonable agreement with our measurements assuming that this molecule has n equal to 9 and contains anchoring groups.…”
Section: Single Molecule Conductancesupporting
confidence: 86%
“…There are only two reports on the single molecule conductance properties of uncharged diazahelicenes, where Nheteroatoms served as the anchoring groups. [30,31] In the first work the theoretical description of mechanical tuning of the single molecule conductance was emphasized, whereas in the second one the single molecule conductance of oxa [9]helicene terminated by pyridine units was reported to be 8.8 × 10 À 4 G/G 0 (log(G/G 0 ) = À 3.06), which is in reasonable agreement with our measurements assuming that this molecule has n equal to 9 and contains anchoring groups.…”
Section: Single Molecule Conductancesupporting
confidence: 86%
“…It thus appeared that ( M )‐ 17 a is prone to oxygenation on sites other that its iodine atoms, notably on positions 9 and 10 of the helicene framework (see Scheme and the Supporting Information). This unfortunate sensitivity of ( M )‐ 17 a toward oxygenation is corroborated by the electrochemical studies of Storch and his colleagues, who recently reported that [7]carbohelicenes are more sensitive to oxidation than their smaller [5] and [6]helicene counterparts . Nevertheless, the conversion of carvacrol ( 18 ) into biscarvacrol ( 19 ) clearly indicated that the bis‐iodinated helicene ( M )‐ 17 a could be in part transformed into an iodosyl (ArIO) or an iodyl (ArIO 2 ) species, which was capable of transferring an oxygen atom onto a 2‐methylphenol substrate with a moderate but real level of enantiocontrol (see Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…This unfortunate sensitivity of (M)-17 a toward oxygenationi sc orroboratedb yt he electrochemical studies of Storch and his colleagues, who recently reported that [7]carbohelicenes are more sensitive to oxidation than their smaller [5] and [6]helicene counterparts. [34] Nevertheless, the conversionofcarvacrol(18)into biscarvacrol (19)clearly indicatedt hat the bis-iodinated helicene (M)-17 a could be in part transformed into an iodosyl (ArIO) or an iodyl (ArIO 2 )s pecies, which was capable of transferringa no xygen atom onto a 2-methylphenol substrate with am oderate but real level of enantiocontrol (see Scheme 7). However,t he low yield of the reaction, the use of the iodane reagent in stoichiometric amountsa nd the difficulties of producing it in pure form were arguments against the continuation of this work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations